Numerical simulation data of an elongated cavitation bubble induced by long-pulsed laser - Xuning Zhao; Wentao Ma; Kevin Wang (Data in Brief, 2023)
The simulation data presented in this paper describes the formation and growth of an elongated bubble induced by a long-pulsed laser. The simulation is performed using the M2C solver, which is a recently developed three-dimensional finite volume Navier-Stokes CFD solver. The solver is used to simulate the fluid dynamics of the liquid water, the laser radiation, the laser-induced vaporization, and the fluid dynamics of the bubble after its formation. The data presented in this paper corresponds to a representative case of the cavitation induced by a narrow Gaussian beam (cf. [1]). Simulation data include laser radiance, fluid velocity, pressure, temperature, and bubble dynamics. The input files and the workflow to perform this simulation are also provided. With the information provided in this paper, researchers can repeat this simulation, and use it as a starting point to study related problems involving laser-induced cavitation, continuous vaporization, and bubble dynamics in general.